Liquid Chromatography–Mass Spectrometry and Chemometric Analysis of Ricinus communis Extracts for Cultivar Identification. Issue 5 (16th April 2014) - Ovenden, Simon P. B.; Pigott, Eloise J.; Rochfort, Simone; Bourne, David J.
ABSTRACT Introduction Seeds of Ricinus communis contain the toxic protein ricin, a 64 kD heterodimeric type II ribosome‐inactivating protein that has been used in several high‐profile poisoning incidents. The ability to determine which cultivar the toxin was isolated from via an LC–MS method would be of significant use to law enforcement and forensic agencies. Objective To analyse via LC–MS and chemometrics (principal components analysis (PCA), orthogonal partial‐least‐squares discriminant analysis (OPLS‐DA)) extracts of R. communis to identify compounds specific to a particular cultivar. Methods Seeds from eight specimens of six cultivars of R. communis ('carmencita', 'dehradun', 'gibsonii', 'impala', 'sanguineus' and 'zanzibariensis') were extracted using a standard methodology. These extracts were analysed by LC–MS then subjected to chemometric analysis (PCA and OPLS‐DA). Identified compounds of importance were subjected to high‐resolution Fourier transform (HRFT) MS and MS/MS to elucidate their structures. Results This analysis identified 17 ions as potential cultivar determinators. Through accurate mass measurement and MS/MS, molecular formulae for 13 ions were determined, including two known and 11 new peptides. Conclusion Unique ions in extracts of 'carmencita', 'dehradun', 'gibsonii', 'impala' and 'zanzibariensis' were identified that would allow an individual cultivar to be distinguished from other cultivars in this study. Although 'sanguineus' extracts contained no unique compounds, a unique LC–MS profile would allow for cultivar assignment. Copyright © 2014 John Wiley & Sons, Ltd.